Low-temperature curing type conductive silver-coated copper slurry for photovoltaic cell and preparation method of low-temperature curing type conductive silver-coated copper slurry
By optimizing the components and preparation methods of the copper slurry of the banking bag, the problem of conductivity, contact and weather resistance in the process of low temperature curing in the existing technologies has been solved, and more efficient conductivity and more efficient conductivity and more efficient conductivity and more efficient conductivity and more Good use performance reduces silver consumption.
Patent Information
- Application Number
- CN202411518970.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-24
AI Technical Summary
The silver-clad copper paste used in existing photovoltaic cells lacks conductivity, contactability and weather resistance during low-temperature curing, resulting in poor performance of HJT photovoltaic cells.
By optimizing the components and preparation methods of the copper slurry of the bank, including the use of micron ball -shaped and Asian micron -shaped coin -shaped coin -shaped copper powder, sheets -shaped coin -based copper powder and sliced silver powder, and add epoxy resin, auxiliary resin and Organic covering agent, through the process such as ultrasonic dispersing and three -roller grinding, prepare low -temperature curing coin -type coin -type coin -type coin -type coin -type coin -type coin -type bronze pulp with excellent conductivity, adhesion, printing, and tactile.
It significantly improves the conductivity, thixotropy and weather resistance of silver-coated copper slurry, reduces silver consumption, and improves the performance and manufacturing cost of HJT photovoltaic cells.
Smart Images

Figure CN119361243A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaic cell metallization, and in particular relates to a low-temperature curing conductive silver-coated copper slurry for photovoltaic cells and a preparation method thereof. Background Art
[0002] Photovoltaic power generation, as a way to directly convert solar energy into electrical energy, has the advantages of being environmentally friendly and renewable, and is one of the important directions for my country's high-quality development of green and clean energy. Currently, N-type crystalline silicon heterojunction (Heterojunction with Intrinsic Thin Layer, HJT) battery technology has received widespread attention. Its photoelectric conversion efficiency is better than that of traditional P-type crystalline silicon solar cells, and it has the potential to become the development direction of the next generation of high-efficiency photovoltaic power generation.
[0003] Conductive paste is the core auxiliary material used in the manufacture of HJT batteries. It is printed onto the battery cell and treated with a metallization process to form a grid electrode that is in close contact with the battery substrate, which is used to collect and conduct current on the surface of the battery cell.
[0004] Due to the characteristics of the thin film layer structure and to avoid damage to the battery structure, the HJT battery metallization process usually requires the use of low-temperature curing conductive paste as the raw material to form the gate electrode.
[0005] At present, low-temperature silver paste is mainly used as the raw material for printing of gate electrode. Although low-temperature silver paste has high conductivity, the large amount of silver used leads to high silver consumption in the metallization process and high battery manufacturing cost.
[0006] Silver-coated copper paste technology, which uses base metal copper to partially replace silver, has become a feasible solution to reduce silver consumption and battery manufacturing costs. Silver-coated copper metallization technology mainly forms a conductive functional phase by coating silver powder on the surface of copper powder, adding organic carriers such as binders, solvents and additives, and preparing silver-coated copper conductive paste through processes such as mixing and grinding. Silver-coated copper powder is not easily oxidized at low temperatures, and the HJT battery metallization process is usually cured at 200°C. Its low-temperature process can inhibit the oxidation of copper, so silver-coated copper paste can be used to replace low-temperature silver paste.
[0007] When silver-coated copper paste is used to replace pure silver paste, it will have some impact on photovoltaic cells, mainly manifested in the higher resistivity of the paste compared to the pure silver system, the weak bonding of the coating layer leading to the separation of the silver-copper shell-core structure during the slurry adjustment process, the poor coating density leading to poor thermal stability and weather resistance, and poor compatibility with organic carriers. The above problems will have a negative impact on the resistivity, thixotropy, and printability of the silver-coated copper paste, and ultimately affect the actual performance of the HJT battery after the conductive paste is printed on the HJT battery.
[0008] Therefore, it is necessary to provide a low-temperature curing conductive silver-coated copper paste for photovoltaic cells and a preparation method thereof to improve the comprehensive properties of the silver-coated copper paste such as conductivity, contact, adhesion, and printing, so that the silver-coated copper paste is more suitable for use in the metallization process of HJT photovoltaic cells, and ultimately improve the performance of HJT photovoltaic cells. Summary of the invention
[0009] In order to overcome the problems in the background technology, the present invention optimizes the raw materials for preparing silver-coated copper slurry and combines it with a suitable preparation method to prepare silver-coated copper slurry with excellent resistivity, adhesion, printability, thixotropy, etc., which facilitates the printing of the slurry onto HJT photovoltaic cells to form grid line electrodes, thereby improving the actual performance of HJT cells.
[0010] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0011] In one aspect, the present invention provides a low-temperature curing conductive silver-coated copper slurry for photovoltaic cells, wherein the silver-coated copper slurry comprises the following components by mass fraction:
[0012] 50-80% micron spherical silver-coated copper powder, 5-30% submicron spherical silver powder, 1-15% micron flaky silver-coated copper powder, 2-20% micron flaky silver powder, and the balance is an organic carrier, wherein the organic carrier comprises 2-5% epoxy resin and 0.5-1.5% auxiliary resin in a mass fraction of the total mass of the silver-coated copper slurry.
[0013] Preferably, the micron spherical silver-coated copper powder has a particle size D50 of 1.0-6.0 μm and a tap density of 3.0-9.0 g / cm 3 , silver content is 20-40%;
[0014] The submicron spherical silver powder has a particle size D50 of 0.1-1.0 μm and a tap density of 2.0-6.0 g / cm 3 ;
[0015] The micron-sized flaky silver-coated copper powder has a particle size D50 of 1.0-8.0 μm, a thickness of 100-400 nm, and a tap density of 3.0-9.0 g / cm 3 , silver content is 20-40%;
[0016] The micron-sized flaky silver powder has a particle size D50 of 0.8-6.0 μm, a thickness of 50-200 nm, and a tap density of 1.5-6.5 g / cm 3 .
[0017] Preferably, the mass ratio of the silver-coated copper powder to the silver powder is 1.5-10:1, and the total content of silver in the mixed powder of the silver-coated copper powder and the silver powder is 35-65%.
[0018] Preferably, the surfaces of the micron spherical silver-coated copper powder, submicron spherical silver powder, micron flaky silver-coated copper powder and micron flaky silver powder are coated with an organic coating agent, and the organic coating agent is one or more of organic amines, organic acids and esters.
[0019] Preferably, the epoxy resin is one or more of 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, 4,5-epoxytetrahydrophthalic acid diglycidyl ester, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, bisphenol A epoxy resin, bisphenol F epoxy resin, and novolac epoxy resin;
[0020] The epoxy equivalent of the epoxy resin is 100-1000;
[0021] The auxiliary resin is one or more of acrylic resin, polyester resin, chloroacetic resin, polyurethane, and silicone resin;
[0022] The mass ratio of the epoxy resin to the auxiliary resin is 2-10:1.
[0023] Preferably, the organic carrier further comprises an organic solvent with a mass fraction of 2-5% of the total mass of the silver-coated copper slurry, a curing agent with a mass fraction of 0.5-3%, and an organic auxiliary agent with a mass fraction of 0.5-1.5%.
[0024] Preferably, the organic solvent is one or more of diethylene glycol butyl ether acetate, tributyl citrate, dimethyl succinate, dimethyl glutarate, dimethyl adipate, methyl nylonate, propylene glycol methyl ether acetate, diethylene glycol monobutyl ether, diethylene glycol diethyl ether, isophorone, and terpineol.
[0025] Preferably, the curing agent is one or more of boron trifluoride ethylamine complex, acid anhydride, dicyandiamide, and blocked isocyanate.
[0026] Preferably, the organic auxiliary agent includes one or more of γ-glycidyloxypropyltrimethoxysilane, urea accelerator, N,N-dimethylbenzylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 2-ethyl-4-methylimidazole, polyamide wax, and hydrogenated castor oil.
[0027] Another aspect of the present invention provides a method for preparing the above-mentioned silver-coated copper slurry, the preparation method comprising the following steps:
[0028] S1. The epoxy resin and auxiliary resin are added to an organic solvent and heated and stirred at a heating temperature of 60-90 ° C. After the resin is fully dissolved, it is cooled to room temperature to obtain a resin dispersion;
[0029] S2. The curing agent and the organic additive are added to the resin dispersion obtained in step S1, stirred uniformly at room temperature and ultrasonically mixed for 5-20 min to obtain an organic carrier;
[0030] S3. The micron spherical silver-coated copper powder, the submicron spherical silver powder, the micron flaky silver-coated copper powder and the micron flaky silver powder are ultrasonically dispersed and mixed, and then added to the organic carrier obtained in step S2, and stirred and mixed uniformly at room temperature by a homogenizer, the stirring speed is 800-1000rpm, and the stirring time is 3-5min to obtain a preliminarily dispersed coarse mixed silver-coated copper slurry;
[0031] S4. The coarse mixed silver-coated copper slurry obtained in step S3 is put into a three-roll mill for grinding and slurrying, and then vacuum filtered through a 300-600 mesh filter to obtain a low-temperature curing conductive silver-coated copper slurry;
[0032] The three-roll mill has a rotation speed of 50-200 rpm, and the roller gap is adjusted from 60 μm to 5 μm in sequence, and the pulp is rolled 5-10 times at each roller gap;
[0033] The fineness of the low-temperature curing conductive silver-coated copper slurry is less than 10 μm.
[0034] Beneficial effects of the present invention:
[0035] 1. The present invention uses epoxy resin and auxiliary resin in combination, so that when the resin is cured, the resin segments are fully cross-linked to form a three-dimensional network structure, which tightly adheres the conductive phase powder together, which helps to improve the conductivity, thixotropy, weather resistance and other properties of the silver-coated copper paste, among which the improvement in conductivity is more obvious.
[0036] 2. The present invention adopts silver-coated copper powder and silver powder compound with different morphologies and particle sizes, so that different powders are easy to overlap and connect with each other, thereby strengthening the stacking degree and conductive path of the conductive phase powder in the silver-coated copper slurry, reducing the internal void density after the silver-coated copper slurry is solidified, and enhancing the contact effectiveness between the conductive phase powders, which helps to improve the conductivity, thixotropy and other properties of the silver-coated copper slurry.
[0037] 3. The present invention prepares the organic carrier by first heating the epoxy resin and the auxiliary resin and then adding other additives, thereby avoiding the reaction between the curing agent and other additives and the resin, which causes the additives to be consumed in advance and cannot fully exert their effects.
[0038] 4. The present invention uses an organic coating agent to perform surface treatment on the silver-coated copper powder and the silver powder. The organic coating agent is matched with the organic solvent of the slurry, which can enhance the contact effectiveness between the silver-coated copper powder and the silver powder and improve the compatibility between the powder and the organic carrier, so that the silver-coated copper slurry has a higher solid content, good wettability and controllable viscosity, which helps to optimize the conductive properties and printing adaptability of the silver-coated copper slurry.
[0039] 5. In the silver-coated copper slurry of the present invention, the silver layer completely covers the copper particles and is uniform and dense, which is not only beneficial to improving the bonding strength of the silver-copper core-shell structure and ensuring that the slurry mixing process does not separate, but also effectively prevents copper from being oxidized, so that the silver-coated copper slurry has better conductivity and printing adaptability. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The viscosity changes of the embodiments and comparative examples of the present invention under different shear rate conditions, wherein line a is the result of embodiment 4, and line b is the result of comparative example 3.
[0041] Figure 2 The morphology of the interface of the battery silver electrode after printing with the silver-coated copper paste is shown in Figure (a). Figure (b) is printed with the silver-coated copper paste of Example 4, Figure (c) is printed with the silver-coated copper paste of Comparative Example 2, and Figure (d) is printed with the silver-coated copper paste of Comparative Example 3. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with specific embodiments.
[0043] In the examples and comparative examples of the present invention, chemical reagents not otherwise specified were all commercially available analytically pure reagents for the experiments.
[0044] Embodiment 1:
[0045] In this embodiment, the silver-coated copper slurry components include: 50% micron spherical silver-coated copper powder (silver content is 20%), 30% submicron spherical silver powder, 5% micron flaky silver-coated copper powder (silver content is 20%), 5% micron flaky silver powder, 4.5% 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, 1% polyester resin, 1% diethylene glycol butyl ether acetate, 0.6% propylene glycol methyl ether acetate, 0.6% diethylene glycol monobutyl ether, 0.3% diethylene glycol diethyl ether, 1.4% methyl hexahydrophthalic anhydride, 0.1% blocked isocyanate, 0.1% 2,4,6-tris(dimethylaminomethyl)phenol, 0.1% 2-ethyl-4-methylimidazole, 0.2% γ-glycidyloxypropyltrimethoxysilane, and 0.1% polyamide wax.
[0046] In this embodiment, silver-coated copper slurry is prepared according to the following method:
[0047] (1) 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester and polyester resin are added to an organic solvent composed of diethylene glycol butyl ether acetate, propylene glycol methyl ether acetate, diethylene glycol monobutyl ether and diethylene glycol diethyl ether, and heated and stirred with a constant temperature magnetic stirrer. The speed is set to 100 rpm, the heating temperature is 80° C., and the stirring time is 4 hours. After the resin is fully dissolved, it is cooled to room temperature to obtain a resin dispersion.
[0048] (2) Methylhexahydrophthalic anhydride, blocked isocyanate, 2,4,6-tris(dimethylaminomethyl)phenol, 2-ethyl-4-methylimidazole, γ-glycidyloxypropyltrimethoxysilane and polyamide wax are added to the above-mentioned resin dispersion, and a constant temperature magnetic stirrer is used with the speed set at 100 rpm, the temperature at 30°C, and the stirring time for 30 minutes. The mixture is then placed in an ultrasonic cleaner for ultrasonic mixing for 20 minutes to obtain an organic carrier.
[0049] (3) The micron spherical silver-coated copper powder, submicron spherical silver powder, micron flaky silver-coated copper powder and micron flaky silver powder are ultrasonically dispersed and mixed, and added into the above-mentioned organic carrier, and mixed evenly by a homogenizer at room temperature, with a rotation speed of 1000 rpm and a stirring time of 5 min to obtain a preliminarily dispersed coarse mixed silver-coated copper slurry.
[0050] (4) The coarsely mixed silver-coated copper slurry is placed in a three-roll mill for grinding and slurry rolling. The rotation speed is set to 150 rpm. The gaps between the initial roll and the final roll are set to 60 μm, 30 μm, 10 μm, and 5 μm, respectively. The slurry is rolled 5-10 times at each roll gap to achieve a sufficient grinding effect and make the slurry mixed and dispersed evenly. The slurry is then vacuum filtered through a 500-mesh filter to obtain the low-temperature curing conductive silver-coated copper slurry with a slurry fineness of less than 10 μm.
[0051] Embodiment 2:
[0052] In this embodiment, the silver-coated copper slurry components include: 60% micron spherical silver-coated copper powder (silver content is 30%), 6% submicron spherical silver powder, 4% micron flaky silver-coated copper powder (silver content is 30%), 20% micron flaky silver powder, 4% 4,5-epoxytetrahydrophthalic acid diglycidyl ester, 1.5% acrylic resin, 1% diethylene glycol butyl ether acetate, 0.4% tributyl citrate, 0.4% nylon acid methyl ester, 0.5% diethylene glycol diethyl ether, 1.5% methyl nadic anhydride, 0.1% blocked isocyanate, 0.1% N,N-dimethylbenzylamine, 0.1% 2-ethyl-4-methylimidazole, 0.2% γ-glycidyloxypropyltrimethoxysilane, and 0.2% polyamide wax.
[0053] In this embodiment, silver-coated copper slurry is prepared according to the following method:
[0054] (1) 4,5-epoxytetrahydrophthalic acid diglycidyl ester and acrylic resin are added to an organic solvent composed of diethylene glycol butyl ether acetate, tributyl citrate, methyl nylonate and diethylene glycol diethyl ether, and heated and stirred with a constant temperature magnetic stirrer. The speed is set to 100 rpm, the heating temperature is 90° C., and the stirring time is 4 h. After the resin is fully dissolved, it is cooled to room temperature to obtain a resin dispersion.
[0055] (2) Add methyl nadic anhydride, blocked isocyanate, N,N-dimethylbenzylamine, 2-ethyl-4-methylimidazole, γ-glycidyloxypropyltrimethoxysilane and polyamide wax to the above resin dispersion, use a constant temperature magnetic stirrer, set the speed to 100 rpm, the temperature to 30°C, and the stirring time to 30 minutes, then put it into an ultrasonic cleaner for ultrasonic mixing for 10 minutes to obtain an organic carrier.
[0056] (3) The micron spherical silver-coated copper powder, submicron spherical silver powder, micron flaky silver-coated copper powder and micron flaky silver powder are ultrasonically dispersed and mixed, and added to the above-mentioned organic carrier, and mixed evenly by a homogenizer at room temperature, with a rotation speed of 900 rpm and a stirring time of 3 minutes to obtain a preliminarily dispersed coarse mixed silver-coated copper slurry.
[0057] (4) The coarsely mixed silver-coated copper slurry is placed in a three-roll mill for grinding and slurry rolling. The rotation speed is set to 200 rpm. The gap between the initial roll and the final roll is adjusted from 60 to 5 μm from large to small. The slurry is rolled 5 to 10 times at each roll gap to achieve a sufficient grinding effect and make the slurry mixed and dispersed evenly. Then, it is vacuum filtered through a 500-mesh filter to obtain the low-temperature curing conductive silver-coated copper slurry with a slurry fineness of less than 10 μm.
[0058] Embodiment 3:
[0059] In this embodiment, the silver-coated copper slurry components include: 65% micron spherical silver-coated copper powder (silver content is 40%), 8% submicron spherical silver powder, 15% micron flaky silver-coated copper powder (silver content is 40%), 2% micron flaky silver powder, 2.5% bisphenol A type epoxy resin, 1.2% polyurethane, 1.7% tributyl citrate, 0.8% dimethyl adipate, 0.8% diethylene glycol monobutyl ether, 0.8% pineol, 0.6% dicyandiamide, 0.5% blocked isocyanate, 0.3% urea accelerator, 0.4% γ-glycidyloxypropyltrimethoxysilane, and 0.4% polyamide wax.
[0060] In this embodiment, silver-coated copper slurry is prepared according to the following method:
[0061] (1) Add bisphenol A epoxy resin and polyurethane to an organic solvent composed of tributyl citrate, dimethyl adipate, diethylene glycol monobutyl ether and pinene alcohol, and heat and stir with a constant temperature magnetic stirrer. The speed is set to 100 rpm, the heating temperature is 60°C, and the stirring time is 4 hours. After the resin is fully dissolved, cool to room temperature to obtain a resin dispersion.
[0062] (2) Add dicyandiamide, blocked isocyanate, urea accelerator, γ-glycidyloxypropyltrimethoxysilane and polyamide wax to the above resin dispersion, use a constant temperature magnetic stirrer, set the speed to 100 rpm, the temperature to 30°C, and the stirring time to 30 minutes, then put it into an ultrasonic cleaner for ultrasonic mixing for 5 minutes to obtain an organic carrier.
[0063] (3) Ultrasonic dispersion and mixing of micron spherical silver-coated copper powder, submicron spherical silver powder, micron flaky silver-coated copper powder and micron flaky silver powder are added to the organic carrier, and mixed uniformly by a homogenizer at room temperature, with a rotation speed of 800 rpm and a stirring time of 4 min to obtain a preliminarily dispersed coarse mixed silver-coated copper slurry.
[0064] (4) The coarsely mixed silver-coated copper slurry is placed in a three-roll mill for grinding and slurry rolling. The rotation speed is set to 50 rpm. The gap between the initial roll and the final roll is adjusted from 60 to 5 μm from large to small. The slurry is rolled 5 to 10 times at each roll gap to achieve a sufficient grinding effect and make the slurry mixed and dispersed evenly. Then, it is vacuum filtered through a 500-mesh filter to obtain the low-temperature curing conductive silver-coated copper slurry with a slurry fineness of less than 10 μm.
[0065] Embodiment 4:
[0066] In this embodiment, the silver-coated copper slurry components include: 70% micron spherical silver-coated copper powder (silver content is 40%), 10% submicron spherical silver powder, 2% micron flaky silver-coated copper powder (silver content is 40%), 8% micron flaky silver powder, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, 0.8% polyester resin, 1.2% diethylene glycol butyl ether acetate, 0.4% dimethyl succinate, 0.4% propylene glycol methyl ether acetate, 0.8% diethylene glycol diethyl ether, 2.5% methyltetrahydrophthalic anhydride, 0.1% blocked isocyanate, 0.2% boron trifluoride ethylamine complex, 0.4% γ-glycidyl ether oxypropyl trimethoxy silane, and 0.2% hydrogenated castor oil.
[0067] In this embodiment, silver-coated copper slurry is prepared according to the following method:
[0068] (1) 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate and polyester resin are added to an organic solvent composed of diethylene glycol butyl ether acetate, dimethyl succinate, propylene glycol methyl ether acetate and diethylene glycol diethyl ether, and heated and stirred with a constant temperature magnetic stirrer. The speed is set to 100 rpm, the heating temperature is 80° C., and the stirring time is 4 hours. After the resin is fully dissolved, it is cooled to room temperature to obtain a resin dispersion.
[0069] (2) Methyltetrahydrophthalic anhydride, blocked isocyanate, boron trifluoride ethylamine complex, γ-glycidyloxypropyltrimethoxysilane, and hydrogenated castor oil are added to the above resin dispersion, and a constant temperature magnetic stirrer is used with the speed set at 100 rpm, the temperature at 30° C., and the stirring time for 30 min. The mixture is then placed in an ultrasonic cleaner for ultrasonic mixing for 20 min to obtain an organic carrier.
[0070] (3) The micron spherical silver-coated copper powder, submicron spherical silver powder, micron flaky silver-coated copper powder and micron flaky silver powder are ultrasonically dispersed and mixed, and added into the above-mentioned organic carrier, and mixed evenly by a homogenizer at room temperature, with a rotation speed of 1000 rpm and a stirring time of 5 min to obtain a preliminarily dispersed coarse mixed silver-coated copper slurry.
[0071] (4) The coarsely mixed silver-coated copper slurry is placed in a three-roll mill for grinding and slurry rolling. The rotation speed is set to 150 rpm. The gap between the initial roll and the final roll is adjusted from 60 to 5 μm from large to small. The slurry is rolled 5 to 10 times at each roll gap to achieve a sufficient grinding effect and make the slurry mixed and dispersed evenly. Then, it is vacuum filtered through a 500-mesh filter to obtain the low-temperature curing conductive silver-coated copper slurry with a slurry fineness of less than 10 μm.
[0072] Embodiment 5:
[0073] In this embodiment, the silver-coated copper slurry components include: 80% micron spherical silver-coated copper powder (silver content is 40%), 5% submicron spherical silver powder, 1% micron flaky silver-coated copper powder (silver content is 30%), 4% micron flaky silver powder, 5% phenolic epoxy resin, 0.5% chloroacetic resin, 1.2% dimethyl succinate, 0.8% propylene glycol methyl ether acetate, 0.8% diethylene glycol monobutyl ether, 0.5% pineol, 0.3% dicyandiamide, 0.3% blocked isocyanate, 0.2% urea accelerator, 0.2% γ-glycidyloxypropyltrimethoxysilane, and 0.2% hydrogenated castor oil.
[0074] In this embodiment, silver-coated copper slurry is prepared according to the following method:
[0075] (1) Phenolic epoxy resin and chloroacetic resin are added to an organic solvent composed of dimethyl succinate, propylene glycol methyl ether acetate, diethylene glycol monobutyl ether and pinene alcohol, and heated and stirred with a constant temperature magnetic stirrer. The speed is set to 100 rpm, the heating temperature is 80° C., and the stirring time is 4 h. After the resin is fully dissolved, it is cooled to room temperature to obtain a resin dispersion.
[0076] (2) Add dicyandiamide, blocked isocyanate, urea accelerator, γ-glycidyloxypropyltrimethoxysilane and hydrogenated castor oil to the above resin dispersion, use a constant temperature magnetic stirrer, set the speed to 100 rpm, the temperature to 30° C., and the stirring time to 30 min. Then, place the mixture in an ultrasonic cleaner for ultrasonic mixing for 20 min to obtain an organic carrier.
[0077] (3) The micron spherical silver-coated copper powder, submicron spherical silver powder, micron flaky silver-coated copper powder and micron flaky silver powder are ultrasonically dispersed and mixed, and added into the above-mentioned organic carrier, and mixed evenly by a homogenizer at room temperature, with a rotation speed of 1000 rpm and a stirring time of 5 min to obtain a preliminarily dispersed coarse mixed silver-coated copper slurry.
[0078] (4) The coarsely mixed silver-coated copper slurry is placed in a three-roll mill for grinding and slurry rolling. The rotation speed is set to 150 rpm. The gap between the initial roll and the final roll is adjusted from 60 to 5 μm from large to small. The slurry is rolled 5 to 10 times at each roll gap to achieve a sufficient grinding effect and make the slurry mixed and dispersed evenly. Then, it is vacuum filtered through a 500-mesh filter to obtain the low-temperature curing conductive silver-coated copper slurry with a slurry fineness of less than 10 μm.
[0079] Comparative Example 1:
[0080] The slurry was prepared in the same manner as in Example 4, except that the pure silver slurry was prepared in the comparative example, the raw materials did not contain silver-coated copper powder, other additive components remained unchanged, and the submicron spherical silver powder accounted for 70% and the micron flaky silver powder accounted for 20%.
[0081] Comparative Example 2:
[0082] This comparative example adopts the same method as Example 4 to prepare the slurry, except that: in the process of preparing the silver-coated copper slurry in this comparative example, only 90% of the spherical silver-coated copper powder is used, and no flaky silver-coated copper powder, flaky silver powder, or submicron spherical silver powder is added; the other components remain unchanged.
[0083] Comparative Example 3:
[0084] This comparative example adopts the same method as Example 4 to prepare the slurry, except that: during the preparation process of this comparative example, no flaky silver-coated copper powder and flaky silver powder are added, and other additive components remain unchanged, namely, 70% micron spherical silver-coated copper powder and 20% submicron spherical silver powder.
[0085] Comparative Example 4:
[0086] This comparative example adopts the same method as Example 4 to prepare the slurry, except that: in the process of preparing the silver-coated copper slurry in this comparative example, the epoxy resin, auxiliary resin, curing agent and organic additive are added to the organic solvent at the same time and heated.
[0087] Comparative Example 5
[0088] The slurry was prepared in the same manner as in Example 4, except that no auxiliary resin was added during the preparation of the silver-clad copper slurry in this comparative example.
[0089] The silver-coated copper paste prepared in the embodiment and the comparative example was printed on the ITO film by screen printing, and then cured at 200°C for 20 minutes respectively; the volume resistivity was tested by a four-probe method; the contact resistivity was tested by a TLM method using a contact resistivity tester; a hundred-grid test was performed using 3M#600 glue to obtain the adhesion between the paste and the ITO film; the printability was obtained by observing whether the line shape of the gate electrode after printing was uniform, continuous and full; the thixotropy was obtained by using a rheometer to simulate the viscosity change of the silver-coated copper paste after high shear and shear force removal during the printing process, and the viscosity recovery of the paste was tested 1 minute after the shear force was removed; the weather resistance was obtained by testing the change in the volume resistivity value relative to the initial value one month later.
[0090] The above test results are shown in Table 1.
[0091] Table 1
[0092]
[0093]
[0094] It can be seen from Table 1 that the overall performance of the silver-clad copper slurry prepared in the embodiment is better than that of comparative examples 2-5, among which the comprehensive performance improvement effect of embodiment 4 is more obvious. By comparing embodiment 4 with comparative example 1, it can be seen that the present invention uses base metal copper to partially replace silver, which reduces the cost, and the comprehensive performance of the silver-clad copper slurry of the present invention is very close to that of pure silver slurry, which can ensure that the silver-clad copper slurry of the present invention is being used in HJT photovoltaic cells.
[0095] By comparing Comparative Example 3 with Comparative Example 2, it can be seen that the comprehensive performance of the silver-coated copper slurry prepared by using only spherical silver-coated copper powder as the raw material is significantly reduced. Figure 2As shown in (b), compared with Comparative Example 3, in the silver-coated copper slurry of Comparative Example 2, the submicron spherical silver powder is lost to fill the pores, resulting in a large number of large pores inside the slurry after solidification, which seriously affects the effective connection between the conductive phase powders, and its conductive performance is significantly reduced. In addition, the pores on the contact interface will also affect the adhesion of the slurry to the substrate. Since Comparative Example 2 uses silver-coated copper powder as the conductive phase, its stability is poor. When the silver coating layer is thin or cannot completely coat the copper, pores will be generated, causing the copper to gradually oxidize, making the slurry weather resistance and stability worse. Therefore, the volume resistivity of the sample of Comparative Example 2 changes significantly after being placed for one month. It can be seen from the data in the table that the addition of an appropriate amount of small-particle powder can effectively improve the comprehensive performance of the slurry.
[0096] The silver-coated copper slurry prepared in Example 4 is better in conductivity than the slurry without adding flaky silver-coated copper powder and flaky silver powder (Comparative Example 3), because the contact between spherical powders is point contact, while the flaky powders are surface contact. During the slurry curing process, the resin continuously reacts and shrinks in volume, so that the powders are bonded together. The addition of flaky powders can effectively increase the contact area between the conductive phase powders, which is beneficial to enhancing the conductivity of the slurry after curing. Therefore, the body resistivity and contact resistivity of Example 4 are relatively low. Therefore, the selection of conductive phase powders with different morphologies can improve the conductivity of the slurry to a certain extent.
[0097] By comparing Example 4 with Comparative Example 4, it can be seen that the volume resistivity and contact resistivity of Comparative Example 4 are increased, the adhesion and thixotropy are reduced, and the printability is deteriorated. The above results indicate that adding the resin and other additives to an organic solvent and heating them will cause part of the resin and the curing agent to react, making it impossible for the resin and the additives to fully function, thereby adversely affecting the conductivity, adhesion, printability and thixotropy of the slurry.
[0098] By comparing Example 4 with Comparative Example 5, it can be seen that the conductivity and adhesion of Comparative Example 5 are relatively poor. During the curing process of the slurry, the auxiliary resin can undergo a cross-linking reaction with the main epoxy resin to produce volume shrinkage, so that the conductive phase powder is tightly adhered together, which can greatly improve the conductivity of the slurry and the adhesion to the substrate. Since no auxiliary resin is added in Comparative Example 5, its conductivity and adhesion are greatly reduced.
[0099] By selecting the slurries of Example 4 and Comparative Example 3 for viscosity change experiments, the viscosity changes of the slurries under different shear rates are obtained as follows: Figure 1 shown.
[0100] pass Figure 1 It can be seen that after the shear force is removed, Example 4 ( Figure 1 (a line)) and Comparative Example 3 ( Figure 1 (Line b)) recover to 97.5% and 95.2% of the initial viscosity, respectively. In addition, the initial viscosities of the above slurries are 108 Pa·s and 46 Pa·s, respectively, indicating that the addition of flaky powder will significantly increase the initial viscosity of the slurry, but has little effect on the thixotropy of the slurry. The initial viscosity of the slurry can be controlled by adjusting the proportion of flaky silver powder.
[0101] Select the ITO film after the slurry printing of Example 4, Comparative Example 2 and Comparative Example 3, and perform SEM experiment on the gate electrode. The results are as follows: Figure 2 shown.
[0102] pass Figure 2 It can be seen that when preparing the silver-coated copper slurry, silver-coated copper powder and silver powder with different morphologies and particle sizes are compounded (Example 4, such as Figure 2 (a) After the slurry is solidified, different powders can form overlapping and lapped structures. At the same time, the submicron spherical silver powder fills the pores between the micron spherical silver-coated copper powder, which helps to improve the comprehensive performance of the silver-coated copper slurry.
Claims
1. A low-temperature curing conductive silver-coated copper slurry for photovoltaic cells, characterized in that: The silver-clad copper slurry comprises the following components by mass fraction: 50-80% micron spherical silver-coated copper powder, 5-30% submicron spherical silver powder, 1-15% micron flaky silver-coated copper powder, 2-20% micron flaky silver powder, and the balance is an organic carrier, wherein the organic carrier comprises 2-5% epoxy resin and 0.5-1.5% auxiliary resin in a mass fraction of the total mass of the silver-coated copper slurry.
2. The low-temperature curing conductive silver-coated copper slurry for photovoltaic cells according to claim 1, characterized in that: The particle size D50 of the micron spherical silver-coated copper powder is 1.0-6.0 μm, and the tap density is 3.0-9.0 g / cm 3 , silver content is 20-40%; The submicron spherical silver powder has a particle size D50 of 0.1-1.0 μm and a tap density of 2.0-6.0 g / cm 3 ; The micron-sized flaky silver-coated copper powder has a particle size D50 of 1.0-8.0 μm, a thickness of 100-400 nm, and a tap density of 3.0-9.0 g / cm 3 , silver content is 20-40%; The micron-sized flaky silver powder has a particle size D50 of 0.8-6.0 μm, a thickness of 50-200 nm, and a tap density of 1.5-6.5 g / cm 3 .
3. The low-temperature curing conductive silver-coated copper slurry for photovoltaic cells according to claim 1, characterized in that: The mass ratio of the silver-coated copper powder to the silver powder is 1.5-10:1, and the total content of silver in the mixed powder of the silver-coated copper powder and the silver powder is 35-65%.
4. The low-temperature curing conductive silver-coated copper slurry for photovoltaic cells according to claim 1, characterized in that: The surfaces of the micron spherical silver-coated copper powder, submicron spherical silver powder, micron flaky silver-coated copper powder and micron flaky silver powder are coated with an organic coating agent, and the organic coating agent is one or more of organic amines, organic acids and esters.
5. The low-temperature curing conductive silver-coated copper paste for photovoltaic cells according to claim 1, characterized in that: The epoxy resin is one or more of 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester, 4,5-epoxytetrahydrophthalic acid diglycidyl ester, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, bisphenol A epoxy resin, bisphenol F epoxy resin, and novolac epoxy resin; The epoxy equivalent of the epoxy resin is 100-1000; The auxiliary resin is one or more of acrylic resin, polyester resin, chloroacetic resin, polyurethane, and silicone resin; The mass ratio of the epoxy resin to the auxiliary resin is 2-10:
1.
6. The low-temperature curing conductive silver-coated copper paste for photovoltaic cells according to claim 1, characterized in that: The organic carrier also includes an organic solvent with a mass fraction of 2-5% of the total mass of the silver-coated copper slurry, a curing agent with a mass fraction of 0.5-3%, and an organic auxiliary agent with a mass fraction of 0.5-1.5%.
7. The low-temperature curing conductive silver-coated copper paste for photovoltaic cells according to claim 6, characterized in that: The organic solvent is one or more of diethylene glycol butyl ether acetate, tributyl citrate, dimethyl succinate, dimethyl glutarate, dimethyl adipate, methyl nylonate, propylene glycol methyl ether acetate, diethylene glycol monobutyl ether, diethylene glycol diethyl ether, isophorone, and terpineol.
8. The low-temperature curing conductive silver-coated copper paste for photovoltaic cells according to claim 6, characterized in that: The curing agent is one or more of boron trifluoride ethylamine complex, acid anhydride, dicyandiamide, and blocked isocyanate.
9. The low-temperature curing conductive silver-coated copper paste for photovoltaic cells according to claim 6, characterized in that: The organic auxiliary agent includes one or more of γ-glycidyloxypropyltrimethoxysilane, urea accelerator, N,N-dimethylbenzylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 2-ethyl-4-methylimidazole, polyamide wax, and hydrogenated castor oil.
10. A method for preparing a low-temperature curing conductive silver-coated copper slurry for photovoltaic cells according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: S1. The epoxy resin and auxiliary resin are added to an organic solvent and heated and stirred at a heating temperature of 60-90 ° C. After the resin is fully dissolved, it is cooled to room temperature to obtain a resin dispersion; S2. The curing agent and the organic additive are added to the resin dispersion obtained in step S1, stirred uniformly at room temperature and ultrasonically mixed for 5-20 min to obtain an organic carrier; S3. The micron spherical silver-coated copper powder, the submicron spherical silver powder, the micron flaky silver-coated copper powder and the micron flaky silver powder are ultrasonically dispersed and mixed, and then added to the organic carrier obtained in step S2, and stirred and mixed uniformly at room temperature by a homogenizer, the stirring speed is 800-1000rpm, and the stirring time is 3-5min to obtain a preliminarily dispersed coarse mixed silver-coated copper slurry; S4. The coarse mixed silver-coated copper slurry obtained in step S3 is put into a three-roll mill for grinding and slurrying, and then vacuum filtered through a 300-600 mesh filter to obtain a low-temperature curing conductive silver-coated copper slurry; The three-roll mill has a rotation speed of 50-200 rpm, and the roller gap is adjusted from 60 μm to 5 μm in sequence, and the pulp is rolled 5-10 times at each roller gap; The fineness of the low-temperature curing conductive silver-coated copper slurry is less than 10 μm.
Citation Information
Cited By
Silver-coated copper conductive low-temperature slurry and preparation method and application thereof
CN120413132A
Silver-clad copper conductive low-temperature slurry and its preparation method and application
CN120413132B
High-temperature-resistant working sealing silver copper paste for power chip and preparation method of high-temperature-resistant working sealing silver copper paste
CN120480186A
Ultra-low silver-containing silver-coated copper conductive paste and preparation method thereof
CN121812242A
Low-temperature curing silver-coated copper slurry for heterojunction solar cell and preparation method of low-temperature curing silver-coated copper slurry
CN122291135A